2008
DOI: 10.1021/jp8008749
|View full text |Cite
|
Sign up to set email alerts
|

Diffusiophoresis of Concentrated Suspensions of Liquid Drops

Abstract: The diffusiophoresis of concentrated suspensions of liquid drops subject to a small electrolyte gradient is analyzed theoretically at arbitrary levels of surface potential and double-layer thickness. The effect of doublelayer polarization and double-layer overlapping is taken into account. Kuwabara's unit cell model is employed in modeling the suspension system, and a pseudospectral method based on Chebyshev polynomial is adopted to solve the resulting general electrokinetic equations. Key factors are examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…thick EDL and small gap between the particle surface and nanopore wall), the EDL surrounding the charged nanoparticle is compressed by the nanopore wall, and the type I DLP mainly arises from the EDL compression by the boundary. [34,37,38,48] If the EDL compression by the nanopore wall is insignificant, as the ratio a/a p increases, the degree of DLP decreases, leading to the decrease in the induced electrophoresis arising from the DLP-induced electric fields.…”
Section: Effect Of the Particle Surface Charge Density S Pmentioning
confidence: 99%
“…thick EDL and small gap between the particle surface and nanopore wall), the EDL surrounding the charged nanoparticle is compressed by the nanopore wall, and the type I DLP mainly arises from the EDL compression by the boundary. [34,37,38,48] If the EDL compression by the nanopore wall is insignificant, as the ratio a/a p increases, the degree of DLP decreases, leading to the decrease in the induced electrophoresis arising from the DLP-induced electric fields.…”
Section: Effect Of the Particle Surface Charge Density S Pmentioning
confidence: 99%
“…The details can also be found elsewhere. 19,21,22,24,25 ■ RESULTS AND DISCUSSION We first make sure the numerical convergence by checking the grid independence of the calculation results in terms of the solutions do not change anymore with further refinement of the computation domain. It turns out that 120 grid points in the outer porous layer and the suspending medium each are sufficient.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Academic studies of the diffusiophoresis phenomenon can be found on both experimental and theoretical fronts in the literature. ,,, Theoretical studies on diffusiophoresis for rigid particles have been conducted extensively, ranging from a single isolated particle to suspensions, lowly charged to highly charged particle surfaces, finite or thin double layers, with or without a nearby or confining boundary, and so on. ,,,, Nonrigid particles like liquid drops and porous particles were investigated as well. Porous particles in particular, which are permeable to the surrounding electrolyte solution, can be used to model polyelectrolytes like proteins and DNA under certain circumstances, for instance. ,, Their diffusiophoretic behavior have been examined thoroughly in electrolyte solution with or without diffusion potential. On the other hand, there are particles of partial porous nature as well, such as a composite particle with a spherical inner rigid core covered by a concentric outer porous layer of finite thickness. , The outer porous layer can be a natural membrane or an artificial polymer layer, which sometimes is called the “fussy layer” or the “polyelectrolyte layer” .…”
Section: Introductionmentioning
confidence: 99%
“…The spontaneous movement of charged colloids in an electrolyte solution subject to an applied salt gradient, known as diffusiophoresis [1], has been studied recently by many investigators both theoretically [2][3][4][5][6][7][8][9][10][11][12][13] and experimentally [14][15][16][17][18]. Compared to conventional electrophoresis operations, diffusiophoresis has the advantages such as no Joules heat effect [19] and metals in electrical contact [20].…”
Section: Introductionmentioning
confidence: 99%